Voyage of rediscovery : a cultural odyssey through Polynesia - Finney, Ben R. (University of California Press, 1994)
"In the summer of 1985, a mostly Hawaiian crew set out aboard Hokulea, a reconstruction of an ancient double canoe, to demonstrate what skeptics had steadfastly denied: that their ancestors, sailing in canoes and navigating solely by reading the stars, ocean swells, and other natural signs, could intentionally sail across the Pacific, exploring the vast oceanic realm of Polynesia and discovering and settling all the inhabitable islands there. Their odyssey from Hawaii to Aotearoa (New Zealand) and back, through seven archipelagos and across 12,000 nautical miles, dramatically refuted theorists who had declared that because of the unseaworthiness of their canoes and the inaccuracy of their navigational methods, the Polynesians could only have been pushed accidentally to their islands by the vagaries of wind and current." "Voyage of Rediscovery recounts this remarkable journey through the Pacific, describing how the Hawaiian navigator, Nainoa Thompson, guided the canoe over thousands of miles of open ocean without compass, sextant, charts, or any other navigational aids. There are tales of a curiosity attack by sperm whales and of the crew's welcome to Aotearoa by Maori tribesmen who dubbed them their sixth tribe. The experimental approach developed by Ben Finney of reconstructing the ancient voyaging canoes, then testing the canoes and the traditional ways of navigating on long voyages, has transformed our ideas about Polynesian migration. It has also been embraced by Hawaiians and other Polynesians as a way to experience and celebrate their rich ancestral heritage as premier seafarers of the ancient world." "By sailing in the wake of their ancestors, the Hawaiians and other Polynesians who captained, navigated, and crewed Hokulea made the long journey described in Voyage of Rediscovery a truly cultural as well as scientific odyssey of exploration into their ancestral past."--Jacket.